(untitled) (Global Scientific Review, 2026)
Due to the recent popularization and investments, artificial intelligence (AI) has become a mainstream form of tech tool within the last years. This event made way for new advantages as well as real potential risks. Despite its novel introduction to everyday life, AI technology actually has a deep history of progress. World’s first computer is debated to date back to as far as the times of ancient Greece, whereas actual algorithms in digital devices more recognizable as “computers” were more developed around the times of WW2. This was when computer science (CS) started its introduction as a new major at universities and research facilities. Digital, complex algorithms were improved upon, world’s first computer was made in 1945. Finally, in 1956, Dartmouth College officially recognized AI as a field.